Silver Nimesulide Complex in Bacterial Cellulose Membranes as an Innovative Therapeutic Method for Topical Treatment of Skin Squamous Cell Carcinoma - Tuany Zambroti Candido; Raphael Enoque Ferraz de Paiva; Mariana Cecchetto Figueiredo; Lilian de Oliveira Coser; Silmara Cristina Lazarini Frajácomo; Camilla Abbehausen; Izilda Aparecida Cardinalli; Wilton Rogerio Lustri; João Ernesto Carvalho; Ana Lucia Tasca Gois Ruiz; Pedro Paulo Corbi; Carmen Silvia Passos Lima (MDPI AG, 2022)
Oxidative stress and inflammation act on skin squamous cell carcinoma (SSCC) development and progression. Curative therapy for SSCC patients is mainly based on surgical resection, which can cause various sequelae. Silver ions have in vitro activities over tumor cells, while nimesulide has antioxidant and anti-inflammatory activities. This study aimed to evaluate the effects of a silver(I) complex with nimesulide (AgNMS) incorporated in a sustained release device based on bacterial cellulose membrane, named AgNMS@BCM, on topic SSCC treatment. The antiproliferative effect of AgNMS complex was evaluated in the SCC4, SCC15 and FaDu SCC lines. AgNMS complex activity on exposure of phosphatidylserine (PS) residues and multicaspase activation were evaluated on FaDu cells by flow cytometry. The AgNMS@BCM effects were evaluated in a SSCC model induced by 7,12-dimethylbenzanthracene/12-o-tetradecanoyl-phorbol-13-acetate (DMBA/TPA) in mice. Toxicity and tumor size were evaluated throughout the study. AgNMS complex showed antiproliferative activity in SCC15 and FaDu lines in low to moderate concentrations (67.3 µM and 107.3 µM, respectively), and induced multicaspase activation on FaDu cells. The AgNMS@BCM did not induce toxicity and reduced tumor size up to 100%. Thus, the application of AgNMS@BCM was effective and safe in SSCC treatment in mice, and can be seen as a potential and safe agent for topic treatment of SSCC in humans.